An unprecedented non-classical polyinterhalogen anion made of [I2Cl]− and I2 at the 2-(p-tolyl)selenopheno[2, 3-b]pyridinium cation template. (7th November 2022) - Aragoni, M. Carla; Podda, Enrico; Arca, Massimiliano; Pintus, Anna; Lippolis, Vito; Caltagirone, Claudia; Bartz, Ricardo H.; Lenardão, Eder J.; Perin, Gelson; Schumacher, Ricardo F.; Coles, Simon J.; Orton, James B.
Abstract : The H -shaped [I10 Cl4 ] 4− polyhalide is the result of the interplay of directional HBs, XBs and π–π interactions driven by the structural features of the 2-( p -tolyl)selenopheno[2, 3- b ]pyridinium cation template. Abstract : The reactivity between 2-( p -tolyl)selenopheno[2, 3- b ]pyridine (L ) and ICl in MeCN is presented. Single crystal structure analysis revealed the formation of two distinct crystalline materials both featuring the protonated 2-( p -tolyl)selenopheno[2, 3- b ]pyridinium cation [HL ] + . Colourless crystals were identified as the dihydrate salt [HL ]Cl·2H2 O (1 ), and dark-red crystals as compound [HL ] + [I2 Cl] − 3 ·1/2I2 (2 ) that features the peculiar presence of the rare non-classical [I2 Cl] − interhalide. Halogen Bonds (XBs) between the cocrystallized I2 molecule and [I2 Cl] − anions led to the novel overall discrete [I10 Cl4 ] 4− H -shaped polyinterhalide formation, which is stabilized through hydrogen bonds (HBs) with the templating [HL ] + cations. The experimental observations are supported by extensive theoretical calculations at the DFT level that were employed to study the role played by non-covalent interactions in the formation of the presented unique polyinterhalide.